Readiness analysis of archives instruments 3 in 1 model in the effectiveness of dynamic archives management - Try Hikmawan; Budi Santoso; Nani Imaniyati (Record and Library Journal, 2022)
Background of the study: The focus of this problem is to be able to find out the effectiveness and impact received from dynamic archive management in the agency, namely in managing general dynamic archive documents; Purpose: The purpose of this study is to identify the effectiveness of archive management by archive management officers; Method: The method used in this study uses descriptive qualitative methods and uses observation, interviews and documentation techniques; Findings: The readiness of the dynamic archive archive instrument 3 in 1 model can be used in dynamic archive management with the implementation of Creation, Use, Maintenance, and Depreciation; Conclusion: The use of 3 in 1 archival instruments has a positive impact and increases effectiveness in archive management.